Human Decidual Stromal Cells as a Component of the Implantation Niche and a Modulator of Maternal Immunity - Kameliya Vinketova; Milena Mourdjeva; Tsvetelina Oreshkova (Journal of Pregnancy)
The human decidua is a specialized tissue characterized by embryo-receptive properties. It is formed during the secretory phase of menstrual cycle from uterine mucosa termed endometrium. The decidua is composed of glands, immune cells, blood and lymph vessels, and decidual stromal cells (DSCs). In the process of decidualization, which is controlled by oestrogen and progesterone, DSCs acquire specific functions related to recognition, selection, and acceptance of the allogeneic embryo, as well as to development of maternal immune tolerance. In this review we discuss the relationship between the decidualization of DSCs and pathological obstetrical and gynaecological conditions. Moreover, the critical influence of DSCs on local immune cells populations as well as their relationship to the onset and maintenance of immune tolerance is described.